Auroglaucin-related neuroprotective compounds from Vietnamese marine sediment-derived fungus Aspergillus niveoglaucus. Issue 18 (16th September 2020) - Yurchenko, Anton N.; Smetanina, Olga F.; Ivanets, Elena V.; Phan, Trinh Thi Hoai; Ngo, Ngoc Thi Duy; Zhuravleva, Olesya I.; Rasin, Anton B.; Dyshlovoy, Sergey A.; Menchinskaya, Ekaterina S.; Pislyagin, Eugeny A.; von Amsberg, Gunhild; Afiyatullov, Shamil Sh.; et al.
Abstract: Two new auroglaucin-derived compounds, niveoglaucins A (1 ) and B (2 ), together with four known related compounds were isolated from extract of the marine sediment-derived strain of Aspergillus niveoglaucus . The structures of these compounds were determined by 1D and 2D NMR spectroscopy and high resolution MS. The plausible biosynthetic pathway was proposed for new compounds 1 and 2 . The neuroprotective activity in 6-OHDA-induced Parkinson's disease cell model was shown for niveoglaucin A (1 ). Graphical Abstract: